A fundamental understanding of the structures of oxygen defect clusters in UO2+x, U4O9 and U3O7: from the perspective of Tetris cubes. (1st August 2020) - Li, Yangzhong
Abstract: A coherent picture for the structure of oxygen defect clusters is presented for fluorite-based oxides of UO2+x, U4 O9 and U3 O7 using molecular dynamics simulations. The simulations used a universal U-O potential that contained no prior knowledge of any form of defect configurations. The three oxides are found to contain a new type of clusters with <110>-displaced O′ atoms in the cluster center and <111>-displaced O″ atoms in the ends. These clusters are more stable than all previously known clusters, such as the cuboctahedron or split di-interstitials. This type of clusters has multiple configurations that can be conveniently modeled as different stacking permutations of Tetris cubes, where the cube length equals to half of the UO2 lattice parameter. These configurations, as well as all other previously known clusters, can be expressed by a generalized form of nomenclature W(v:n:m). Short and linear Tetris clusters have the lowest formation energies and are the dominant form in UO2+x for 0.1 < x < 0.4. The lattice parameters and the internal alignment of clusters are found to affect each other mutually, and preferential alignment due to steric interaction causes the tetragonalization and phase transformation in U3 O7 . The Tetris model is able to clarify the relationship among the formation of O′/O″ interstitials, the cluster configuration and lattice deformation in a consistent and systematic way for fluorite-based uranium oxides, and is expected to provide new mechanism in explaining atomic transportation in UO2+x . Graphical abstract: Image, graphical abstract